Taxation of Economic Cross-Border Operations for Providing Services in Electronic Form - Georgievich Gurinovich, Alexander; Shakhmametiev, Alexey Alimovich (Indian Journal of Finance, 2023)
Purpose: This paper analyzed the situations in which it was possible to use foreign experience and international standards to increase the efficiency of taxation of cross-border activities for the provision of electronic services in electronic form by an individual state. Methodology: Using economic indicators and official sources, we conducted a generalizing assessment of the fundamental models and ideas of taxation of transactions involving digital products and services generated within the Organization for Economic Cooperation and Development scope. The practical value of these models and ideas used to strengthen the Russian tax system was proved based on their findings. Findings: As a result of an analysis of international standards and rules relating to the taxation of transactions involving digital goods and services, the main principles and algorithms were identified, the use of which at the national level allows for the rapid modernization of the taxation system and adaptation to the challenges of the new (digital) economy. Practical Implications: Taking into account the dynamics of the expansion of the use of digital products not only in business but also in public administration, a practically realizable potential for the application of previously developed international rules in modern conditions was identified, in particular, the possibility of remote interaction between tax authorities and taxpayers. Originality: The paper’s novelty lies in substantiating the possibility of practical application of the basic principles and models of taxation of services in electronic form developed at the international level in states with significant differences in economic development and tax systems. The work’s practical significance lay in identifying the importance of international standards and principles of taxation of electronic services for the development of national rules and creating conditions that impede the development of new forms of economic activity, as well as formulating recommendations for the practical application and improvement of the rules for taxation of electronic services.